The Value of the Customer's Waiting Time for General Queues*. (30th October 2018) - Singhal, Kalyan; Singhal, Jaya; Kumar, Subodha
ABSTRACT: We have developed a measure of the value of the customer's waiting time that is applicable to all queuing systems. Since the birth of the modern queuing theory over 100 years ago, this measure is the first addition to the list of the measures of performance of general queues that includes the servers' utilization factor, the expected queue length, the expected waiting time, and some variations of the last two. The curves for trade‐offs between the servers' utilization factor and the value of the customer's time can be used to supplement or replace the curves for trade‐offs between the servers' utilization factor and the customer's expected queue length (or expected waiting time) that have been a fundamental part of the modern queuing theory. The decisions made with the value of the customer's waiting time will mirror the decision maker's goals more closely than the decisions made with the customer's expected queue length or expected waiting time that are surrogates for the value of the customer's waiting time. Although our definition of the value of the customer's time is deceptively simple, its implications can be significant and far reaching. It could change the way we pursue research in the queuing theory, the way we teach the queuing theory, and the way we design queuing systems in practice.